Urgensi Kompetensi Profesionalisme Guru Dalam Pembentukan Karakter Bagi Anak Usia Dini - Candrawati, Putri; Darmiyanti, Astuti; Munafiah, Nida’ul (Peneliti.net, 2024)
Characters that can be formed in children usually include politeness, affection, friendship, discipline, and independence Instilling character training either intentionally or unintentionally requires alignment with some tasks to complete character instructions. In early childhood education institutions that educate children between 0-6 years. Where at that time it can be said to be the golden period, teacher competence consists of four competencies, the four competencies are competency standards that must be possessed and fulfilled by the teacher, namely: Personal, social, pedagogical and professional competencies are knowledge, abilities and skills that must be possessed by a teacher, Early childhood education in fulfilling its role is largely determined by the teacher or educator. The quality of teacher professionalism determines the awareness of teachers in fulfilling their role optimally as an education provider for children. Professional teachers will realize the importance of fulfilling children's rights that must be protected in order to support children's growth and development as well as possible. Children who are protected both physically, mentally, rights and from deviations will be able to develop their potential optimally without distractions and obstacles. The problem that still occurs in the world of education is the lack of professional competence that teachers have in building children's character or in other words, not meeting the professional competence of teachers.